La teoria del control i els infinitius no controlats - Hernanz, Maria Lluïsa (Caplletra. Revista Internacional de Filologia, 2015)
The purpose of this paper is to analyze a number of syntactic and semantic properties exhibited by a specific class of non controlled infinitivals in Spanish (cf. English "To know him is to love him") and to suggest that they all fall under general assumptions concerning the behaviour of "donkey sentences". More precisely, we show that some instances of PRO(arb) provide a crucial evidence in order to claim that Control Theory interacts with a more general theory of "arbitrary" interpretation.